Antibacterial, biocompatibility and nanomechanical properties of TI-6AL-7NB alloy coated with copper, hydroxyapatite and copper ion doped hydroxyapatite for dental implants - Al-Murshedi, Hanan Ali Hameed (2018)
Implant-associated infection has been a serious clinical problem. An effective absence of surgical associated infection is one of the keys for a successful oral implant therapy. The aims of this study were to evaluate the antibacterial, cytotoxicity, cell attachment and nanoindentation of titanium-6 aluminium-7 niobium (Ti-6Al-7Nb) alloy coated with synthesized copper, hydroxyapatite and copper ion doped hydroxyapatite. The antibacterial performance of coated and uncoated samples on Staphylococcus aureus and Staphylococcus epidermidis was performed using two types of agar (Mannitol Salt Agar (MSA) and Mueller Hinton Agar (MHA)) that was evaluated after day 1, 2 and 3 by disk diffusion test. In addition, antibacterial properties of coated and uncoated samples on Porphyromonas gingivalis, S. aureus and S. epidermidis were compared after day 1, 2 and 3 by disk diffusion and broth culture tests. Statistical analysis was performed using repeated-ANOVA (P< 0.05). The effect of cell toxicity and function of coated and uncoated samples were assessed using methyl-thiazol-diphenyltetrazolium (MTT) assay on human fetal osteoblast (hFOB) cells after 24 and 72 hours. One-way analysis of variance (ANOVA) followed by post-hoc multiple comparisons analysis using Scheffe test were used. The cell morphology and attachment were evaluated after 24 and 72 hours using inverted microscope and observed under SEM respectively. Furthermore, the effectsof nCu addition on hardness and elastic modulus of coated layer was investigated by nanoindentation. Statistical analysis was completed using Kruskal-Wallis test (P< 0.05). The results showed that the antibacterial evaluation using agar diffusion and broth culture tests indicated that Ti Cu and Ti Cu/HA significantly inhibit the growth of S. aureus, S. epidermidis and P. gingivalis while Ti and Ti HA demonstrated no antibacterial effect. Additionally, MSA yielded comparable result to MHA when used as the medium for testing bacterial susceptibility using agar diffusion test. The MTT assay showed that Cu content on the surface of Ti-6Al-7Nb alloys has no cytotoxic effect on cell viability. The cell viability rate for Ti Cu/HA was kept at significantly higher value on day 3 as compared to day 1, indicating that hFOB cells grow at a high proliferation rate. Microscopic evaluation indicated no differences in the cell morphology among all samples. Under SEM, the cell attachment properties for all samples were favourable. Nevertheless, hFOB cells attached and formed more bridges on Ti HA and Ti Cu/HA compared to Ti and Ti Cu groups. The nanoindentation results confirmed that the hardness and elastic modulus of HA were significantly improved by incorporating nCu. In conclusion, the results suggest that the surface modification of Ti-6Al-7Nb alloy with nCu/HA may be good for local control of infection for dental implant with no adverse effect on the cytotoxicity of hFOB cells. Also, the addition of nCu may be recommended to improve the nanomechanical properties of the coating layer to Ti-6Al-7Nb alloy.